Development of Project-Based Learning (PjBL) Teaching Module for the Basic of Metrology Course in the Mechanical Engineering Education Study Program at Sriwijaya University - Efri Meldianto; Wadirin Wadirin; Puteri Anggieta Cahyani; Romy Saputra; Ainun Maulidina; Yogi Herdianto; Nopriyanti Nopriyanti; Farhan Yadi; Mochamad Amri Santosa; Sapitri Januariyansah (Jurnal Vokasi Mekanika (VoMek), 2025)
The focus of this research aims to design a learning module based on the principles of Project Based Learning (PjBL) for the Basic Metrology course in the Mechanical Engineering Education Study Program, Sriwijaya University. Utilizing a Research and Development (R&D) methodology, the study adopts the 4D model, encompassing the stages of Define, Design, Develop, and Disseminate. Validation by a subject matter expert produced an average rating of 3.50 (87.5%), classifying the module as highly valid. Concurrently, evaluation by a media expert yielded an average score of 3.25 (81.37%), situating it within the valid category. Furthermore, a practicality assessment derived from student feedback returned an average score of 3.32 (83.25%), which is categorized as excellent. In the component of creativity and innovation, the module received a score of 3.00 or 75%, suggesting that although the module functions well, there remains room for enhancement to further encourage students’ ability to generate new ideas.